Jaffe-Lichtenstein Syndrome Associated with a Simple Bone Cyst: Unprecedented Rare Case Report - Miranda,Poliana Gonçalves (2020)
Abstract Lesions denominated fibro-osseous lesions of the jaw constitute a diversified group of disorders, in which the normal bone architecture is replaced by fibroblasts, collagen fibers and immature bone. At present, the World Health Organization recognizes four variants of these lesions, namely: bone-cement dysplasia, fibrous dysplasia, ossifying fibroma and Familial gigantiform cementoma. Fibrous dysplasia may present in the monostotic form, affecting one single bone or an isolated craniofacial region; and in the Polyostotic form, involving two or more bones of the skeleton, and eventual association with syndromic conditions. The patient, C.P.G., 43 years old, sought attendance due to symptomatic increase in the region of the mandibular body on the right side. Imaging exams revealed craniofacial areas with ground-glass aspect, beyond the extensive mandibular radiolucent lesion. During the physical exam, spots of the Café au lait type disposed on the right side of the body were identified, in addition to uncoordinated gait with distinct shortening of the right leg. Additional radiographic exams showed evidence of skeletal dissemination of the disease. The patient denied any sexual precocity, and the final diagnosis was fibrous dysplasia, expressed by means of the Jaffe-Lichtenstein syndrome, in association with a simple bone cyst.